Spatially modulated structural colour in bird feathers - Andrew J. Parnell; Adam L. Washington; Oleksandr O. Mykhaylyk; Christopher J. Hill; Antonino Bianco; Stephanie L. Burg; Andrew J. C. Dennison; Mary Snape; Ashley J. Cadby; Andrew Smith; Sylvain Prevost; David M. Whittaker; et al. (Scientific Reports)
Abstract Eurasian Jay (Garrulus glandarius) feathers display periodic variations in the reflected colour from white through light blue, dark blue and black. We find the structures responsible for the colour are continuous in their size and spatially controlled by the degree of spinodal phase separation in the corresponding region of the feather barb. Blue structures have a well-defined broadband ultra-violet (UV) to blue wavelength distribution; the corresponding nanostructure has characteristic spinodal morphology with a lengthscale of order 150 nm. White regions have a larger 200 nm nanostructure, consistent with a spinodal process that has coarsened further, yielding broader wavelength white reflectance. Our analysis shows that nanostructure in single bird feather barbs can be varied continuously by controlling the time the keratin network is allowed to phase separate before mobility in the system is arrested. Dynamic scaling analysis of the single barb scattering data implies that the phase separation arrest mechanism is rapid and also distinct from the spinodal phase separation mechanism i.e. it is not gelation or intermolecular re-association. Any growing lengthscale using this spinodal phase separation approach must first traverse the UV and blue wavelength regions, growing the structure by coarsening, resulting in a broad distribution of domain sizes.